Quantum Chemistry PM3 Calculations of Sixteen mEGF Molecules (Journal of Atomic and Molecular Sciences, 2018)
Murine epidermal growth factor (mEGF) is a single polypeptide of fifty-three amino acid residues containing three intramolecular disulfide bonds, widely found in body fluids like milk. We performed semi-empirical quantum chemistry calculations on sixteen mEGF molecules at level of PM3 to investigate the electronic properties of these molecules. The equilibrium structure, heats of formation, molecular orbitals, polarizability, and dipole moment were computed in vacuum and in solvents (carbon tetrachloride, ethanol, and water). Electronic structure calculations in vacuum show that the highest occupied molecular orbital (HOMO) of all mEGF molecules distributes on five C-terminal residues (Tyr49/Tyr50 and Arg48/Arg53 residues), while the lowest unoccupied molecular orbital (LUMO) locates on the disulfide bonds, indicating that the disulfide bridges and C-terminus are important for the biological activity of EGF. The locations of LUMO and HOMO show almost no solvent effects. In the solvent of relative larger dielectric constant, the heat of formation and mean polarizability of the mEGF molecules become lower while the dipole moment is enhanced. Examination of the locations of hydrogen bonds demonstrates that the B loop (residues 14-31) is crucial for the conformational stability and biological activity of EGF. All these theoretical results are in general agreement with experiments. We suspect that the N- and C-terminal residues play some roles in stabilizing the molecular conformation of EGF, probably associated with the orientation of EGF binding to EGFR (epidermal growth factor receptor).